SUGGESTIONS TO THE COMMISSION ON ORGANIZATION OF THE EXECUTIVE BRANCH OF THE GOVERNMENT. - Bordner, Howard W. (The Accounting Review, 1948)
Abstract The creation of the Commission on Organization of the Executive Branch of the Government by authority of the Congress of the United States is but one of many attempts to reorganize extensively the Executive Branch of the United States Government. The Commission is composed of twelve members representing the President of the United States, the Senate, and the House of Representatives. While the General Accounting Office is an agency of the Legislative Branch, it is impossible to disregard its functions in any study of accounting in the Executive Branch of the government, especially as to the placement of certain responsibilities and avoidance of duplication of effort. The suggestion has just been made that the powers of prescribing methods of accounting disallowing expenditures do not properly pertain to auditing. It is desired also to make certain comments with respect to the audit responsibilities of the General Accounting Office in part from the standpoint of the placement of responsibilities between the Legislative and Executive Branches and in part from the standpoint of indicating that greater benefits may be obtained from independent auditing.